The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1074/jbc.m113.492694
|View full text |Cite
|
Sign up to set email alerts
|

Redox-regulated Cargo Binding and Release by the Peroxisomal Targeting Signal Receptor, Pex5

Abstract: Background: Pex5 transports PTS1 proteins to peroxisomes, releases them there, and returns to the cytosol. Results: Several steps of the import cycle are controlled by redox-sensitive oligomeric states of Pex5. Conclusion: Cargo release from Pex5 is achieved by a redox-regulated oligomer to dimer transition of Pex5 and aided by Pex8. Significance: This redox regulation of Pex5 function provides the first mechanistic view of cargo release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 39 publications
3
52
1
Order By: Relevance
“…These results contrast previous reports indicating that LdPEX5 tended to form a tetramer [33]. This difference in quaternary structure is likely due to disulfide bond formation as previously documented [38]. A similar analysis of ldpex14 showed that this fragment eluted as ~35 kDa species, a size corresponding to a homodimer [25].…”
Section: Quaternary Structure Of Ldpex5-ldpex14 Complexescontrasting
confidence: 99%
“…These results contrast previous reports indicating that LdPEX5 tended to form a tetramer [33]. This difference in quaternary structure is likely due to disulfide bond formation as previously documented [38]. A similar analysis of ldpex14 showed that this fragment eluted as ~35 kDa species, a size corresponding to a homodimer [25].…”
Section: Quaternary Structure Of Ldpex5-ldpex14 Complexescontrasting
confidence: 99%
“…36 One surprising observation is that the binding affinity of all the peptides tested in the present study was, within experimental error, identical for both truncated and full length PEX5. Since the N terminally truncated PEX5C lacks this redox sensitive Cys such a mechanism would appear not to be relevant in the context of the binding of short peptides in our experimental system.…”
Section: Implications For Cargo Binding To Pex5mentioning
confidence: 55%
“…Observations made for the Hansenula polymorpha Pex5p by fluorescence analysis revealed that the protein is a monomer at pH 6.0 and a tetramer at pH 7.2 (55, 56). According to SEC and SDS- PAGE under non-reducing conditions, Pex5p of Leishmania donovani and Pichia pastoris forms a tetramer of two dimers (57,58). Thus, the unusual migration behavior of yeast Pex5p upon SEC in light of the clear indication that the protein is monomeric by light scattering adds to the peculiar behavior of Pex5p from other species, and in analogy to its human orthologue it is best explained by the assumption that yeast Pex5p is monomeric with an unfolded N-terminal half.…”
Section: Discussionmentioning
confidence: 99%